A one-step process employing various amphiphiles for an electrically insulating silica coating on graphite. Issue 39 (3rd May 2017) - Kim, Yeongseon; Qian, Yingjie; Kim, Minjae; Ju, Jaechul; Baeck, Sung-Hyeon; Shim, Sang Eun
Abstract : Herein, we report new way and mechanism to completely coat graphite (3–550 μm) with a silica layer within 12 hours. Abstract : Ceramic coatings endow carbon materials with electrically insulating properties. For graphite, it is unclear whether ceramic coatings applied via a one-step process under mild conditions can lead to superior coverage. This paper reports that a modified Stöber method with an appropriate choice of amphiphiles could yield an electrically insulating coating layer on graphite ( d 50 3–300 μm, d 90 6–550 μm) within 24 h with high reproducibility. A silica coating mechanism involving functional groups on the edge of the graphite, Oswald ripening agents, and a bridgemer was investigated. The mechanism was based on the silica coating morphology, which depends on the amphiphile, and the correlation between coverage and surface resistivity was assessed. Amphiphile-assisted silica@graphite with a surface resistivity of 10 12 ohm sq −1 was produced. The thermal conductivity of the silica-coated graphite (amphiphile-assisted silica@graphite)/TPEE composite reached values over 75% higher than that of the raw graphite/TPEE composite with electrically insulating properties.